2017
DOI: 10.1016/j.radonc.2017.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multi-leaf collimator tracking and treatment-couch tracking during stereotactic body radiation therapy of prostate cancer

Abstract: MLC and couch tracking at a conventional linear accelerator significantly improved the accuracy of prostate SBRT in the presence of motion, whereby couch tracking showed slightly better performance than MLC tracking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
(34 reference statements)
1
15
1
Order By: Relevance
“…Compared to previous studies at other institutions using the same tracking system, 54,55 the dosimetric performance of MLC tracking presented in this paper is inferior. The difference could be attributed mainly to two reasons, differences in motion characteristics and treatment plans.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Compared to previous studies at other institutions using the same tracking system, 54,55 the dosimetric performance of MLC tracking presented in this paper is inferior. The difference could be attributed mainly to two reasons, differences in motion characteristics and treatment plans.…”
Section: Discussioncontrasting
confidence: 73%
“…A similar comparison study for prostate SBRT using the same system was reported by Ehrbar et al where couch tracking showed generally better performance compared to MLC tracking. 55 The vast majority of publications of MLC and couch tracking focus on lung and prostate cases, but limited studies have been reported for abdominal cancers, 56 which are also significantly affected by respiratory motion and other physiological motion in the gastrointestinal track. In this study, we evaluated the accuracy of both MLC and couch tracking for pancreas and liver diseases using Varian iTools Tracking.…”
Section: Introductionmentioning
confidence: 99%
“…Motion mitigation is an obvious application of motion monitoring and several mitigation methods have been compared in different treatment sites (Menten et al 2012 , Ehrbar et al 2016 , 2017a , Colvill et al 2016 , Toftegaard et al 2017 , Nankali et al 2018 ). Another application of motion monitoring is real-time dose reconstruction which can provide real-time QA for treatments delivered with or without mitigation (Ravkilde et al 2014 , 2018 , Kamerling et al 2016a , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…With those dosimetry systems, the performance of couch tracking was evaluated. This has been done before, but so far only in rigid phantoms 12,42 or phantoms with rigidly moving tumors. 43 As can be seen from Fig.…”
Section: Discussionmentioning
confidence: 99%